Test report no. PLBO/9: comparison of PERPRO tools RD92 against Sanvik S1P under roughing conditions - College of Aeronautics, (Cranfield) (College of Aeronautics, 1964)
Tools of grade RD92 and S1P were tested to 0.030 in. flank wear when machining EN9 at 300 fpm with 0.030 in/rev, feed and 0.10 in. depth of cut. The results showed that while there was no significant difference in tool life between the two grades, RD92 suffered greater crater wear and nose deformation than did S1P.